Ideological storms : intellectuals, dictators, and the totalitarian temptation - Tismaneanu, Vladimir; Iacob, Bogdan (Central European University Press, 2019)
This volume gathers authors who wrote important works in the fields of the history of ideologies, the comparative study of dictatorships, and intellectual history. The book is a state of the art reassessment and analysis of the ideological commitments of intellectuals and their relationships with dictatorships during the twentieth century. The contributions focus on turning points or moments of breakage as well as on the continuities. Though its focus is on an East-West comparison in Europe, there are texts also dealing with Latin America, China, and the Middle East giving the book a global ou.